Sulforaphane induces S-phase arrest and apoptosis via p53-dependent manner in gastric cancer cells - Wang, Yuan; Wu, Huazhang; Dong, Nannan; Su, Xu; Duan, Mingxiu; Wei, Yaqin; Wei, Jun; Liu, Gaofeng; Peng, Qingjie; Zhao, Yunli (Scientific reports, 2021)
Sulforaphane (SFN) extracted from broccoli sprout has previously been investigated for its potential properties in cancers, however, the underlying mechanisms of the anticancer activity of SFN remain not fully understood. In the present study, we investigate the effects of SFN on cell proliferation, cell cycle, cell apoptosis, and also the expression of several cell cycle and apoptosis-related genes by MTT assay, flow cytometry and western blot analysis in gastric cancer (GC) cells. The results showed that SFN could impair the colony-forming ability in BGC-823 and MGC-803 cell lines compared with the control. In addition, SFN significantly suppressed cell proliferation by arresting the cell cycle at the S phase and enhancing cell apoptosis in GC cells in a dose-dependent manner. Western blot results showed that SFN treatment significantly increased the expression levels of p53, p21 and decreased CDK2 expression, which directly regulated the S phase transition. The Bax and cleaved-caspase-3 genes involved in apoptosis executive functions were significantly increased in a dose-dependent manner in BGC-823 and MGC-803 cells. These results suggested that SFN-induced S phase cell cycle arrest and apoptosis through p53-dependent manner in GC cells, which suggested that SFN has a potential therapeutic application in the treatment and prevention of GC.